93.9k views
2 votes
F(x) = Square root of quantity x plus nine. ; g(x) = 8x - 13 Find f(g(x)). (1 point)

User Enthuziast
by
4.2k points

1 Answer

3 votes


f(g(x)) = 2√(2x-1)

Solution:

Given that,


f(x) = √(x+9)\\\\g(x) = 8x - 13

We have to find f(g(x))

Which means, substitute g(x) value in place of x in f(x)

Therefore,


f(g(x)) = √(8x - 13 + 9)\\\\Simplify\\\\f(g(x)) = √(8x -4)\\\\Take\ common\ factor\ out\\\\f(g(x)) = √(4(2x-1))\\\\f(g(x)) = 2√(2x-1)

Thus f(g(x)) is found

User Marinos
by
5.5k points